Comparison of critical factor affecting the germination of rice seeds treated by LASER and plasma. Issue 9 (3rd October 2022) - Iqbal, Tahir; Salim, Muhammad; Afsheen, Sumera; Abrar, Muhammad; Naseer, Hira; Qureshi, Muhammad Tauseef; Hameed, Reda S. Abdel; Mohamed, D.; Al Elaimi, Mahmoud; Soliman, Mahmoud Shafik
Abstract : The effects of laser (single, double, and triple pulse laser) and plasma treatment (time and voltage variation) on rice seeds (KS-186) with and without seed coat are investigated in this research work. Germination rate, fungus attack, root to stem ratio and water absorption was explored. The germination rate of the seeds reached 86% and maximum water absorption for 3- and 4-min plasma treated seeds whereas 100% growth rate is observed for single pulsed LASER treated leads to best root to stem ratio. In contract to the LASER treatment, there was no fungus attack on seeds with seed coat treated with plasma as compared to untreated seed coat. The protein analysis reveals that nutritional contents of seeds were enhanced due to irradiation by laser.